Policy Communication Of Licensing Business Swallow’s Nests In Pekanbaru City - rinaldy may wendra; Teuku Afrizal; Endang Larasati; Tri Yuniningsih (Jurnal Ilmiah Ilmu Administrasi Publik, 2020)
Communication in the policy implementation process is intended so that all stakeholders involved can understand and show attitudes and provide responses to the policy implementation process. Poor communication between the stakeholders involved will only create ineffectiveness in the policy implementation process. This study aims to analyze the communication in the policy of managing and exploiting swallow's nests in Pekanbaru. This research is a qualitative descriptive study, with data collection techniques using interviews, documentation and observation. Communication on the implementation of the business permit policy for managing and exploiting swallow's nest in Pekanbaru City is seen from the process of delivering information to policy implementers and target groups, as well as being analyzed from the aspects of the communication media used and the accuracy and clarity of the information received. The delivery of information about policies to policy implementers is quite good, but communication to the sasarang group is not optimal with communication media in the form of socialization that is not yet effective.